AB0373 Sarcopenia could not predict falls in patients with rheumatoid arthritis from the chikara study. (12th June 2018) - Tada, M.; Yamada, Y.; Mandai, K.; Hidaka, N.
Abstract : Background: The falls ratio is higher among patients with sarcopenia than among healthy individuals. We reported that the prevalence of sarcopenia was 28% and locomotive syndrome (locomo) was 52% in patients with rheumatoid arthritis (RA) 1 . Whether patients with RA complicated by sarcopenia show a higher ratio of falls compared to those without sarcopenia remains unclear. Objectives: We investigated events of falls and fractures, and predictors of those events in patients with RA. Methods: We used data from a prospective observational study (CHIKARA study, UMIN000023744) started in 2016. Sarcopenia was diagnosed using the criteria of the Asia Working Group on Sarcopenia 2 . We counted the number of patients and events of falls and fractures they had per year[A1], and investigated correlations between those events and disease activity, body composition and sarcopenia. Predictors at baseline influencing those events were analysed by uni- and multivariate analysis. Results: Participants comprised 100 patients with RA (females, 78%; mean age, 66.1 years). Falls occurred in 21 patients (19 women), as 33 events (mean, 2 times/patient). Fractures occurred in 4 patients (4 women), as 5 events. Table 1 shows predictors for falls, with positive correlations for bone mass index, obesity level, fat percentage, and locomo, and negative correlations for height, trunk muscle mass, and grip strength. No relationships were seen between falls and CRP, DAS28ESR, skeletal muscle mass, and sarcopenia. Height (odds ratio, 0.912; p=0.003) and obesity level (odds ratio, 1.04; p=0.006) were independent predictors by multivariate analysis (table 1). In terms of fracture events, falls was the only predictor (r=0.469, p=0.001). Conclusions: Falls have been reported as significantly more frequent with sarcopenia. However, no relationship was seen between fall events and sarcopenia in this study. We may need to evaluate not only skeletal muscle mass, but also muscle function to predict falls. References: [1] Tada M, Yamada Y, Mandai K, et al. Relationship of matrix metalloprotease 3 titer and sarcopenia in patients with rheumatoid arthritis: data from the CHIKARA study. Eular2017:abstract THU0157. [2] Chen LK, Liu LK, Assantachai P, et al. Sarcopenia in Asia: consensus report of the Asian Working Group for Sarcopenia. J Am Med Dir Assoc2014;15:95–101. Disclosure of Interest: None declared